Astilbin Inhibits High Glucose-Induced Inflammation and Extracellular Matrix Accumulation by Suppressing the TLR4/MyD88/NF-κB Pathway in Rat Glomerular Mesangial Cells - Chen, Fang; Zhu, Xiaoguang; Sun, Zhiqiang; Ma, Yali (Frontiers in Pharmacology, 2018)
Diabetic nephropathy (DN) is characterized by inflammatory responses and extracellular matrix (ECM) accumulation. Astilbin is an active natural compound and possesses anti-inflammatory activity. The aim of this study was to evaluate the anti-inflammatory effect of astilbin on high glucose (HG)-induced glomerular mesangial cells and the potential mechanisms. The results showed that HG induced cell proliferation of HBZY-1 cells in a time-dependent manner, and astilbin inhibited HG-induced cell proliferation. The expression and secretion of inflammatory cytokines, including interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α), and ECM components, including collagen IV (Col IV) and fibronectin (FN), were induced by HG. Moreover, TGF-β1 and CTGF were also induced by HG. The induction by HG on inflammatory response and ECM accumulation was inhibited after astilbin treatment. Astilbin treatment also attenuated HG-induced decrease in expression of matrix metalloproteinase (MMP)-2 and MMP-9. The TLR4/MyD88/NF-κB pathway was activated by HG, and the inhibitor of TLR4 exhibited the same effect to astilbin on reversing the induction of HG. TLR4 overexpression attenuated the effect of astilbin on HG-induced inflammatory cytokine production and ECM accumulation. The results suggested that astilbin attenuated inflammation and ECM accumulation in HG-induced rat glomerular mesangial cells via inhibiting the TLR4/MyD88/NF-κB pathway. This work provided evidence that astilbin can be considered as a potential candidate for DN therapy.